Diabetes management self-efficacy and glycaemic control among people with type 2 diabetes in a resource-limited setting - Idongesit L. Jackson; Unyime I. Eshiet; Samuel I. Onung; Esther S. Egbe (Discover Public Health)
Abstract Background The ability of people with diabetes to perform diabetes self-care activities may influence treatment outcomes. Objectives To evaluate diabetes management self-efficacy (DMSE) and short-term glycaemic control among people with type 2 diabetes (PWT2D). Methods This was a cross-sectional survey of 238 PWT2D at the University of Uyo Teaching Hospital, Nigeria. DMSE was assessed using the Diabetes Management Self-Efficacy Scale—UK version (DMSES UK). Glycaemic control was assessed with fasting blood glucose (FBG). Data were analysed using SPSS v.25.0. Results The median (IQR) self-efficacy score was 115 (91–125) out of 150. DMSE was highest for blood/urine sugar testing, hypoglycaemia correction, feet examination, and medication taking (median score = 10 out of 10). Only 6.3% and 11.3% of participants, respectively, reported high self-efficacy for adjusting their eating pattern/plan when stressed/anxious or when exercising more. The mean FBG was 8.5 ± 4.3 mmol/L, with 45% of participants having good glycaemic control (4.4–7.2 mmol/L). Participants’ sex (p = 0.001) and education (p = 0.031) were significantly associated with DMSE. DMSE showed a negative correlation with FBG (rs = − 0.68, p < 0.001). Conclusion Efforts to promote self-efficacy in healthy eating in various situations may improve glycaemic control in PWT2D, especially women and those with low levels of education.